Gene expression profiling of epithelium-associated FcRL4+ B cells in primary Sjögren's syndrome reveals a pathogenic signature. Issue 109 (May 2020) - Verstappen, Gwenny M.; Ice, John A.; Bootsma, Hendrika; Pringle, Sarah; Haacke, Erlin A.; de Lange, Kim; van der Vries, Gerben B.; Hickey, Peter; Vissink, Arjan; Spijkervet, Frederik K.L.; Lessard, Christopher J.; Kroese, Frans G.M.
Abstract: In primary Sjögren's syndrome (pSS), FcRL4 + B cells are present in inflamed salivary gland tissue, within or in close proximity to ductal epithelium. FcRL4 is also expressed by nearly all pSS-related mucosa-associated lymphoid tissue (MALT) B cell lymphomas, linking FcRL4 expression to lymphomagenesis. Whether glandular FcRL4 + B cells are pathogenic, how these cells originate, and how they functionally differ from FcRL4 - B cells in pSS is unclear. This study aimed to investigate the phenotype and function of FcRL4 + B cells in the periphery and parotid gland tissue of patients with pSS. First, circulating FcRL4 + B cells from 44 pSS and 54 non–SS–sicca patients were analyzed by flow cytometry. Additionally, RNA sequencing of FcRL4 + B cells sorted from parotid gland cell suspensions of 6 pSS patients was performed. B cells were sorted from cell suspensions as mini bulk (5 cells/well) based on the following definitions: CD19 + CD27 − FcRL4 - ('naive'), CD19 + CD27 + FcRL4 - ('memory'), and CD19 + FcRL4 + B cells. We found that, although FcRL4 + B cells were not enriched in blood in pSS compared with non-SS sicca patients, these cells generally exhibited a pro-inflammatory phenotype. Genes coding for CD11c ( ITGAX ), T-bet ( TBX21 ), TACI ( TNFRSF13B ), Src tyrosine kinases and NF-κB pathway-related genes were, among others, significantly upregulated in glandular FcRL4 + B cells versus FcRL4 - B cells. Pathway analysis showed upregulation of B cell activation, cell cycle and metabolic pathways. Thus, FcRL4 + B cells in pSS exhibit many characteristics of chronically activated, pro-inflammatory B cells and their gene expression profile suggests increased risk of lymphomagenesis. We postulate that these cells contribute significantly to the epithelial damage seen in the glandular tissue and that FcRL4 + B cells are an important treatment target in pSS. Highlights: Epithelium-associated B cells in parotid glands of pSS patients are highly activated. Glandular FcRL4 + B cells express the pro-inflammatory markers CD11c and T-bet. NF-κB activation and IL-6 secretion are pathogenic features of FcRL4 + cells in pSS. The activation profile of FcRL4 + B cells suggests increased risk of lymphomagenesis.